Using Virtual Reality for Long-Duration Space Missions - Joshi, Yash; Mardon, Austin (Technium Social Sciences Journal, 2021)
Many organizations around the world are pursuing space exploration with hopes of going further and further away from Earth. Spaceflight itself has significant implications on humans, meaning that it is important to understand the magnitude of effects that astronauts would feel during these missions. Some pressing concerns are the increased isolation due to social interactions as well as situational factors, which would lead to a decline in mental and physical health. Additionally, the possibility of substance abuse due to stress and access to medications can lead to significant reductions in mental health. To deal with these issues, virtual reality has presented itself as a unique solution that would help provide better overall mental health. The technology is frequently used in various clinical settings to deal with anxiety and depression, through techniques such as exposure therapy and cognitive behavioural therapy. Exposure therapy for anxiety with virtual reality targets anxiety-causing stimulus and works towards changing the patient’s response, in a controlled setting. Cognitive behavioural therapy immerses the patient into a simulated world to provide them with experiences that mitigate the depression they are feeling. On the mission, exposure therapy would potentially be available to deal with stimulants of anxiety, while cognitive behavioural therapy would provide a happiness break. With further research in the field, virtual reality thus presents itself as a feasible opportunity to plan longer duration human space missions. This review compiles and investigates sources from literary research done in the respective fields.